PETROGRAPHIC, MINERALOGICAL AND GEOMECHANICAL CHARACTERIZATION OF SANDSTONES EXPLOITED IN QUARRIES IN KINSHASA - Jonathan Musitu Muliwavyo; Raissa Nzita; Innocent Mufungizi; Albert Mbata Muliwavyo; Lumière Musitu; Jean Kabulo; Trésor Hube rt; Jimy Musitu Berka; Ivon Ndala Tshiwisa; Clement N’zau Umba-Di-Mbudi; Junior Lutete Savu (Geological Behavior, 2024)
The sandstone of Inkisi, serving as support for infrastructure and construction materials in the city province of Kinshasa, is of interest for geomechanical studies in particular and geological studies in general. Given its outcrop almost everywhere in Kinshasa and its high consumption in the field of buildings and public works, we have set ourselves the main goal of its macroscopic petrographic characterization and on thin sections using a polarizing microscope, mineralogical by X-ray diffraction and geomechanical by Simple and Los Angeles compression tests using quarry samples from the Kimwenza and Kinsuka sandstones. Petrographically, they are essentially arkosic sandstones. X-ray diffraction reveals the abundance of quartz in our sandstones. It also allowed the detection of minerals containing titanium in addition to feldspars. The simple compression test showed that these sandstones follow mode A from the point of view of rupture and that these sandstones belong to the class of medium strength from the point of view of the classification of resistance to simple compression. The Los Angeles test suggests that these sandstones have a coefficient in the good to average range. And therefore, on a geomechanical level, the sandstones studied in the two quarries of Kimwenza and Kinsuka are suitable for various construction works.